Prognostic value of KRAS/TP53/PIK3CA in non-small cell lung cancer - Zhao, Jiayi (Oncol Lett, 2019)
The present study explored the association between KRAS proto-oncogene GTPase (KRAS), phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit α (PIK3CA) and tumor protein p53 (TP53) mutations, and the clinical features and survival prognosis in 50 patients with non-small cell lung cancer (NSCLC). The most common concurrent single gene mutation was TP53, followed by KRAS and PIK3CA. Co-existing mutations were found in 17 patients. KRAS, PIK3CA and TP53 mutations were associated with carbohydrate antigen 19-9 expression, invasive growth, vacuolar signs and margin lobulation on chest CT. The incidence of distant metastasis (bone and adrenal) with KRAS and TP53 mutations was greater than that of local metastasis (pleura). Patients with the wild-type genes experienced longer progression-free survival (PFS) times than those with KRAS, TP53, KRAS/TP53 or PIK3CA/TP53 mutations. Patients with KRAS/TP53 or PIK3CA/TP53 mutations experienced shorter PFS times than those with a single KRAS or TP53 mutation. KRAS, PIK3CA and TP53 mutations were associated with distant metastases and a poor prognosis. Patients with NSCLC should receive routine KRAS, PIK3CA and TP53 gene sequencing to determine mutations for the analysis of clinical characteristics and prognosis.